Budapesti polgárság - Ránki, György (Tér és Társadalom, 1990)
Naturally, our investigations on the Hungarian bourgeoisie are limited by the fact that the concept and statistical description of bourgeoisie are very difficult to determine and show. Lines of division within bourgeoisie are even more difficult – if possible at all – to draw, though they are needed to grasp the stratification of bourgeoisie and the number of people belonging to petit and middle bourgeoisie. In the first case, we are faced with an important socio-historical problem: due to the specific development of Hungarian society, can and if yes to what , extent be civil servants considered part of the bourgeoisie. It is well known that the Hungarian state apparatus, in the beginning of its development, was filled up in the majority with the earlier noble people. Even later, when people with noble origin were not dominant, the strata of civil servants could be distinguished from economic bourgeoisie clearly in respect of their social norms, behaviour, political concepts and attitude as the later represented bourgeois ethos much more, and civil servants rather identified themselves with the traditional political ruling class and the landowners. As a consequence of all these, the Hungarian interpretation usually does not consider civil servants part of the bourgeoisie. This view appears at Ferenc Erdei as well, who argues that "the state dominated the lower society as an all-mighty power, state power became an almost independent conservative power". In summary we can conclude, that if we add the number of independents (7-8 thousand), private and civil servants (12-15 thousand) and intellectuals (8-10 thousand) then the number of middle and haute bourgeois families living in Budapest could be determined at around 30-35 thousand.